Molecular Epidemiology of Extended-Spectrum β-Lactamase–Producing Escherichia coli Pathotypes in Diarrheal Children from Low Socioeconomic Status Communities in Bihar, India: Emergence of the CTX-M Type. (6th November 2017) - Mandal, Abhishek; Sengupta, Abhishek; Kumar, Ajay; Singh, Utpal K; Jaiswal, Anil K; Das, Pradeep; Das, Sushmita
Background: Childhood diarrheal diseases remain highly endemic in India, but the emergence of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli among children with diarrhea in Bihar remains elusive. In this study, we determine and characterize ESBL-producing E coli pathotypes among hospitalized diarrheal preschool children living in low socioeconomic level communities in Bihar, India. Materials and methods: The stool samples were collected everyday throughout the year for 2 consecutive years. In our study, we collected stool samples randomly from every fifth patient. Stool samples were collected from a total of 633 randomly selected diarrheal children (age: 0-60 months) belonging to 17 communities and screened for identification of virulent diarrheagenic E coli (DEC) pathotype (viz, enteropathogenic E coli [EPEC], enteroaggregative E coli [EAEC], enterotoxigenic E coli [ETEC], enteroinvasive E coli [EIEC], and enterohemorrhagic E coli [EHEC]) by a multiplex polymerase chain reaction (PCR) assay. Furthermore, ESBLs were screened by conventional antibiotic resistance pattern testing and later characterized for the presence of β-lactamase ( bla ) genes by PCR and DNA sequencing. Results: Diarrheagenic E coli was detected in 191 cases (30.2%) of the total 633 diarrheic children. Maximum occurrence of DEC was found in ≤12 months age group (72.7%) with prevalence of the EAEC pathotype. Most isolates were resistant to ampicillin, ciprofloxacin, piperacillin, levofloxacin, ceftazidime, cefotaxime, ceftriaxone, and gentamicin, whereas over 96% of them were sensitive to amikacin. About 37.6% of total 191 DEC isolates were ESBL producers (n = 72), being prevalent among ETEC (n = 35; 18.32%), followed by EPEC (n = 21; 10.9%), EAEC (n = 13; 6.8%), and EIEC (n = 3; 1.57%). Interestingly, the commonest β-lactamase was CTX-M type ( bla CTX-M ) in 86.1% (n = 62) of the ESBL isolates, followed by bla SHV (n = 49; 68%), bla TEM (n = 37; 51.8%), and bla OXA (n = 21; 29.1%) determinants. Resistance of ESBL isolates was mostly related to ampicillin (100%), ceftriaxone (98.1%), cefotaxime (92.4%), gentamicin (74.1%), and levofloxacin (73.2%), whereas best antimicrobial activities were observed for piperacillin-tazobactam, amikacin, meropenem, and imipenem. Conclusions: This study revealed that EAEC (72.1%) is the predominant pathotype in Bihar, significantly high in ≤12 months age group children ( P = .04). Moreover, the widespread prevalence of ESBLs in children, especially the CTX-M type, is of great concern, which requires monitoring of infection control measures through efficient antimicrobial management and detection of ESBL-producing isolates.